(untitled) (Global Journal of Science Frontier Research, 2016)
On the basis of pertinent in-situ measurements in the North Sea during extra-tropical cyclones and in the Gulf of Mexico during Hurricane Rita, a power law relation between overwater friction velocity and the wind speed at 10m is found and presented. Since the coefficient of determination exceeds 94 per cent, this power law is recommended for use in air-sea interaction studies.